Actor and Partner Effects of Touch: Touch-Induced Stress Alleviation Is Influenced by Perceived Relationship Quality of the Couple - Liu, Difei; Piao, Yi; Ma, Ru; Zhang, Yongjun; Guo, Wen; Zuo, Lin; Liu, Weili; Song, Hongwen; Zhang, Xiaochu (Frontiers in Psychology, 2021)
Because of the impact of close partner’s touch on psychological and physical well-being by alleviating stress, it is important to explore the influence factors that underlie the stress alleviating effect of close partner’s touch. The previous studies suggested that the stress alleviating effect was different when individuals were touched by different persons. Specifically, the stress was reduced significantly when the individual was touched by close partners compared with the acquaintance and the stranger. However, whether the stress alleviating effect of touch was modulated by the close relationship quality is unknown. To examine this question, the participants (n=61) performed a three (i.e., alone, partner no-touch, and partner touch) by two (i.e., safety, and threat) within-subjects experiment. Results revealed the stress of participants alleviated significantly while close partners present with touch than without touch during facing with threat. We also found that the relationship quality of the couple-members (i.e., participants perceiving quality of alternatives and the partners’ commitment level) modulated touch-induced stress alleviation. Participants perceiving the low quality of alternatives and the high partners’ commitment level, showed the stronger touch-induced stress alleviating effect compared with participants perceiving the high quality of alternatives and the low partners’ commitment level. The explained variance was around 16.8% jointly for actor and partner effects. These findings provide evidence for explaining the reasons for touch-induced alleviating stress and have important implications for predicting the future effect of interactive behaviors.